Effect of Organic Waste Concentration on Reactor Performance in Anaerobic Co-Fermentation of Wastewater of Tofu Industry and Organic Solid Waste - Sofyan Sofyan; Salmariza Salmariza (Jurnal Litbang Industri, 2015)
Fuel crisis of oil and gas that are faced currently requires a thought to look for an alternative energy. The objective of this study was to observe the effect of organic waste addition on reactor performance and to increase the production of biogas as an alternative renewable energy. The wastewater used was the wastewater from agglomeration of soy pulp in tofu industry, while the solid waste used was a mixture of organic waste from household and market waste. The study was conducted by fermenting the wastewater and organic waste together with sample volume 300 ml. The reactors were operated semi-continuously with substrate feeding every two weeks. The treatment used in this study were mass comparison of organic waste and wastewater (0:100)%; (5:95)%; (10:90)%; (20:80)%; (30:70)%; and (40:60)%. The results showed that the addition of organic waste affected the reactor performance and the amount of biogas produced. Anaerobic co-fermentation of wastewater from tofu industry and organic waste produced biogas more than fermentation of wastewater without organic waste. The highest amount of biogas was obtained in the treatment of organic waste addition as much as 30% with average volume of biogas was 728 ml in steady state condition.ABSTRAKKrisis bahan bakar minyak dan gas yang dihadapi saat ini memerlukan pemikiran untuk mencari energi alternatif. Penelitian ini bertujuan untuk mengamati pengaruh penambahan sampah organik terhadap kinerja reaktor anaerobik dan meningkatkan produksi biogas sebagai salah satu energi alternatif terbarukan. Limbah cair yang digunakan adalah limbah cair dari penggumpalan bubur kedelai pada industri tahu, sedangkan sampah organik yang digunakan adalah gabungan sampah organik dari rumah tangga dan sampah pasar. Penelitian dilakukan dengan mendigestasi limbah cair industri tahu dan sampah organik secara bersama-sama dalam reaktor anaerobik dengan volume sampel 300 ml. Reaktor dioperasikan secara semi kontinyu dengan pengumpanan substrat setiap dua minggu sekali. Perlakuan yang dilakukan adalah perbandingan massa sampah organik dan limbah cair yaitu (0:100)%; (5:95)%; (10:90)%; (20:80)%; (30:70)%; dan (40:60)%. Hasil penelitian menunjukkan bahwa penambahan sampah organik mempengaruhi kinerja reaktor dan jumlah biogas yang dihasilkan. Fermentasi anaerobik limbah cair industri tahu dan sampah organik menghasilkan biogas lebih banyak dibandingkan dengan fermentasi limbah cair industri tahu tanpa sampah organik. Jumlah biogas terbanyak diperoleh pada perlakuan penambahan sampah organik 30% dengan volume biogas rata-rata 728 ml pada kondisi tunak.